A preliminary study on the monitoring of mixed venous oxygen saturation through the left main bronchus - Wang, Xiang-rui; Zheng, Yong-jun; Tian, Jie; Wang, Zheng-hong; Pan, Zhi-ying (Critical care (London, England), 2006)
The study sought to assess the feasibility and accuracy of measuring mixed venous oxygen saturation (SvO2) through the left main bronchus (SpO2(trachea)) Twenty hybrid pigs of each sex were studied. After anesthesia, a Robertshaw double-lumen tracheal tube with a single-use pediatric pulse oximeter attached to the left lateral surface was introduced toward the left main bronchus of the pig by means of a fibrobronchoscope. Measurements of SpO2(trachea) and oxygen saturation from pulmonary artery samples (SvO2(blood)) were performed with an intracuff pressure of 0 to 60 cmH2O. After equilibration, hemorrhagic shock was induced in these pigs by bleeding to a mean arterial blood pressure of 40 mmHg. With the intracuff pressure maintained at 60 cmH2O, SpO2(trachea) and SvO2(blood) were obtained respectively during the pre-shock period, immediately after the onset of shock, 15 and 30 minutes after shock, and 15, 30, and 60 minutes after resuscitation. SpO2(trachea) was the same as SvO2(blood) at an intracuff pressure of 10, 20, 40, and 60 cmH2O, but was reduced when the intracuff pressure was zero (p < 0.001 compared with SvO2(blood)) in hemodynamically stable states. Changes of SpO2(trachea) and SvO2(blood) corresponded with varieties of cardiac output during the hemorrhagic shock period. There was a significant correlation between the two methods at different time points. Measurement of the left main bronchus SpO2 is feasible and provides similar readings to SvO2(blood) in hemodynamically stable or in low saturation states. Tracheal oximetry readings are not primarily derived from the tracheal mucosa. The technique merits further evaluation.